ICT training during initial teacher preparation: a comparative study across socioeconomic regions of Paraguay - Cañete-Estigarribia, Lucía; Castillo-Vega, José (Revista Innova Educación, 2025)
This comparative study analyzes the initial teacher training in Paraguay regarding the use of Information and Communication Technologies (ICT) across different socioeconomic regions of the country. A quantitative approach was employed, with a descriptive scope and a non-experimental, cross-sectional design. The sample consisted of 476 prospective teachers from 11 officially managed teacher training institutes nationwide. The findings reveal significant convergences and divergences concerning the availability of technological resources, the training received, and attitudes toward ICT. The Central-Southern region shows the greatest shortage of technological resources, although all regions share the need to improve technological infrastructure and training in the use of these technologies. Despite these limitations, prospective teachers express positive attitudes toward ICT, which is a key factor for their effective integration into the educational process and for improving the quality of teaching. Consequently, it is concluded that policies should be implemented to promote an equitable distribution of technological resources and ensure continuous training, especially in the most disadvantaged regions. Moreover, fostering the effective integration of ICT in the classroom is crucial, taking into account the positive attitudes of future teachers. Achieving this requires a comprehensive approach that addresses regional disparities in resources, training, and attitudes, in order to promote quality education that meets the demands of the 21st century throughout Paraguay.